Ecological status of Ganoderma and basal stem rot disease of oil palms (Elaeis guineensis Jacq.) - Naher, Laila; Yusuf, Umi Kalsom; Ismail, Ahmad; Tan, Soon Guan; Mondal, Mohd Monjurul Alam (Southern Cross Publishing, 2013)
The bracket fungus, Ganoderma boninense Pat., causes basal stem rot (BSR) disease in oil palm plants. Previously the disease was reported only in older age palms and currently found on young stages palms as well. Therefore, Ganoderma can infect all stages of oil palm plants. Disease symptoms only appear at the late stage of the disease and usually called a silent killer of oil palm. Progression of the disease is slow; however, it can destroy thousands of hectares of oil palm plantations. Basal stem rot shortens the productive life of oil palms and causes serious economic losses to the oil palm industry. Hence, BSR is considered a serious threat to the oil palm industry in South East Asian countries. To date, there is high demand for sustainable detection and control of this disease. This review paper is elaborated on the detection and ecological impact of Ganoderma and BSR disease in oil palms plantation.